The Existence of Higher Education in Indonesia as a Public Service Agency in the Implementation of Good University Governance - Ismet Sulila (Journal of International Conference Proceedings, 2021)
Higher education autonomy can be realized if universities carry out good university governance. Gorontalo State University (UNG) in Indonesia has implemented the governance of the Public Service Agency (BLU) in recent years. However, an empirical study of its existence as a BLU has not been implemented. The existence of UNG as a BLU in Gorontalo Province is expected to be able to provide the best service in the tri dharma of academics based on the principles of Good University Governance. This study aims to examine the implementation of the concepts and principles of Public Service Bodies in Higher Education in terms of the principles of Good University Governance. The methodology used is descriptive qualitative which includes: desk study, field visits and in-depth interviews, presentations and discussions of study results to answer the research focus. The results of the study found that 1) The implementation of the concept of the University Public Service Board for Gorontalo State University has been carried out through the application of the principles of Good University Governance which consist of: a) Transparency, b) Accountability, c) Responsibility, d) Independency, e) Fairness. 2) The factors that determine the effectiveness of Gorontalo State University as a Public Service Agency consist of: a) Gorontalo State University strategic policies, b) Gorontalo State University innovation as a tertiary institution, c) Gorontalo State University academic support. 3) Third: Development of tertiary institutions as Public Service Bodies based on the four pillars of leadership of the Gorontalo State University Chancellor is carried out through: a) Achieving educational quality through accreditation, b) Achieving Research Quality and Community Service, c) National and international cooperation, d) improving the quality of graduates . This research contributes to the development of higher education in general in implementing Good University Governance.